Development of glow discharge and electron cyclotron resonance heating conditioning on W7-X. (January 2019) - Goriaev, A.; Wauters, T.; Brakel, R.; Grote, H.; Gruca, M.; Volzke, O.; Brezinsek, S.; Dinklage, A.; Kubkowska, M.; Neuner, U.
Highlights: GDC and ECRH wall conditioning was routinely used during the first divertor campaign. H2 –GDC was conducted to sustain the satisfactory amount of impurities outgassing. He–GDC was chosen to desaturate the wall from hydrogen prior to plasma operation. He–ECRH wall conditioning was used for density control when the magnetic field was on. High-energetic long single recovery discharges remove less hydrogen than pulse trains. Abstract: For successful operation of Wendelstein 7-X (W7-X) control of plasma impurity content and fuel recycling is required. This can be achieved by using wall conditioning methods. During the first divertor operation campaign (OP1.2a) of W7-X glow discharge conditioning (GDC), weekly in hydrogen and daily in helium for impurity and hydrogen removal respectively, was used in the absence of the magnetic field. He electron cyclotron resonance heating (ECRH) discharges were applied for density control in hydrogen plasmas during experimental days. The optimization of GDC and He ECRH wall conditioning on W7-X are presented. Solutions for glow discharge ignition problems are examined. The suitable He – GDC parameters, i.e. anode current and neutral gas pressure, are defined to keep the balance between maximum possible hydrogen removal rate and minimum plasma – facing component (PFC) erosion. Sequences of short He – ECRH pulses, so-called pulse trains, has been successfully implemented. The effect of pulse train main parameter variation such as gas prefill, input power, pulse length, duty cycle is described. The efficiency of single He recovery discharges and pulse trains are compared. The results of this work show significant improvement of wall cleaning efficiency.